Consumer Behavior Toward Nonlocal Brands - Sana Aza; Amina Talat; Feryal Khan; Anam Rana (The Lahore Journal of Business)
This study explores consumer behavior toward nonlocal brands in Pakistan. Specifically, it examines the extent to which (i) product quality, (ii) country of origin, (iii) religiosity (in the context of Pakistan as a predominantly Muslim country), (iv) social status, and (v) the unavailability of local substitutes determine consumers’ purchasing decisions. Consumer ethnocentrism and the desire to emulate economically developed country lifestyles serve as the study’s moderating variables. The research data was collected through a questionnaire survey conducted in Lahore among a sample of 200 people between the ages of 18 and 55. The questionnaires were distributed via Google Docs and employed a convenience and snowball sample. A confirmatory factor analysis was carried out to establish reliability and validity. The structured model was then used to assess the relationships identified above.